Grief after suicide in Pandemic Times - Mora Mora, Paula (2025)
The present essay addresses grief due to suicide in pandemic times, connecting studies by Marleny Campos, Taryn Torres, and Roxana Alemán in La Cruz, Guanacaste (October 2021); Helga Arroyo and Damián Herrera in the Bribri indigenous territory (2019); and the November 19, 2021, discussion with Kimberly Vargas titled "The Last Coffee, the Talk I Always Wanted Us to Have." Suicide is presented as an expression of pain resulting from social rupture, with multiple causes. The goal is to understand grief over suicide through social constructionism and liberation psychology. The methodology combines analysis of previous research, participation in an academic forum, and personal reflections. Results show an increase in suicides and attempts during the pandemic, changes in farewell rituals, and increased emotional isolation. The analysis highlights the need to give new meaning to losses and use sensitive language to break stigma and support the grieving process. Conclusions call for strengthening personal and community bonds, fostering cultural and psychological support spaces, and developing public policies that integrate professional and community assistance to mitigate the grief crisis and prevent suicide in socially vulnerable contexts such as those created by the pandemic.